Endo/Lysosome‐Escapable Delivery Depot for Improving BBB Transcytosis and Neuron Targeted Therapy of Alzheimer's Disease. (15th May 2020) - Cai, Lulu; Yang, Chuanyao; Jia, Wenfeng; Liu, Yuwei; Xie, Rou; Lei, Ting; Yang, Zhihang; He, Xueqin; Tong, Rongsheng; Gao, Huile
Abstract: The effective treatment of Alzheimer's disease (AD) is hindered due to the hard blood–brain barrier (BBB) penetration and non‐selective distribution of drugs in the brain. Moreover, the complicated pathological mechanism of AD involves various pathway dysfunctions that limit the effectiveness of a single therapeutic drug. Herein, a dendrigraft poly‐l ‐lysines (DGL)‐based siRNA and D peptide (Dp) loaded nanoparticle is designed that could target and penetrate through the BBB, enter the brain parenchyma, and further accumulate at the AD lesion. In this system, T7 peptide, which specifically targets transferrin receptors on the BBB, is linked to DGL via acid‐cleavable long polyethylene glycol (PEG) to achieve high internalization, quick escape from endo/lysosome, and effective transcytosis. Then, the Tet1, which specifically targets diseased neurons, is modified onto DGL by short PEG. After being exposed, Tet1 could drive the nanoparticles to the AD lesion and release the drugs. As a result, the production of β amyloid plaques (Aβ) is inhibited. Neurotoxicity induced by Aβ plaques and tau proten phosphorylation (p‐tau) tangle is also alleviated, and the cognition of AD mice is significantly improved. Overall, this system programmatically targets BBB and neurons, thus, significantly enhances the intracephalic drug accumulation and AD treatment efficacy. Abstract : A dendrigraft poly‐l ‐lysines‐based BACE siRNA and D peptide loaded nanoparticle are designed, which can target and penetrate through the blood–brain barrier by a long chain acid‐cleavable PEG‐T7, and further accumulate in brain neurons by a short chain PEG‐Tet1. This nanoparticle can significantly enhance the intracephalic drug accumulation and Alzheimer's disease treatment efficacy.